2017
DOI: 10.1557/jmr.2017.352
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and hardness properties of laser clad Ni base two-phase intermetallic alloy coating

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similar research findings have been reported in the literature [29][30][31], and all of these works confirm the good applicability of Ni-based alloys for laser cladding materials. Other Nibased coatings, such as NiCoCrAlYSi coatings on GH4169 [32] and NiAlVNbB coatings on SUS304 [33], have also been produced.…”
Section: Introductionmentioning
confidence: 99%
“…Similar research findings have been reported in the literature [29][30][31], and all of these works confirm the good applicability of Ni-based alloys for laser cladding materials. Other Nibased coatings, such as NiCoCrAlYSi coatings on GH4169 [32] and NiAlVNbB coatings on SUS304 [33], have also been produced.…”
Section: Introductionmentioning
confidence: 99%